The Regional Security Puzzle around Afghanistan Bordering Practices in Central Asia and Beyond - Rytövuori-Apunen, Helena (Verlag Barbara Budrich, 2016)
Western military presence wanes in Afghanistan and a transformed security environment challenges borders and stability in Central Asia. This book examines how the tensions relating to the reorganization of external military presence interact with regional states' ambitions and challenge the borders already contested by numerous dividing lines. It studies a complex political landscape across which radical Islam connected with international terrorism is feared to spread as the international mission initiated in the wake of the 9/11 attacks winds down.